Simple current-mode analog multiplier, divider, square-rooter and squarer based on CDTAs - Tangsrirat, Worapong; Pukkalanun, Tattaya; Mongkolwai, Pratya; Surakampontorn, Wanlop (My University, 2011)
In this paper, the design of simple analog current-mode multiplier, divider, square-rooter and squarer circuits using only two current differencing transconductance amplifiers (CDTAs) is proposed. With the selection of the applied input currents, the proposed circuit can perform four-quadrant current multiplication, division and current-controlled current amplification, without changing its configuration. Moreover, the current-mode square-rooter and squarer circuits can easily be obtained with the possibility of electronically transfer gain adjustment by slight modification of the proposed configuration. All the proposed circuits are insensitive to ambient temperature variations. Additionally, the CDTA non-ideality effects on the proposed circuits are also investigated and discussed. The performances of the realized circuits are examined by PSPICE simulations. © 2010 Elsevier GmbH. All rights reserved.
Keywords: Current differencing transconductance amplifier (CDTA); Current-mode circuits; Divider, Square-rooter; Multiplier; Squarer